A sustentabilidade na comunicação visual: uma análise dos elementos visuais de empresas de moda sustentável - (:unkn) unknown (Universidade Federal do Pampa, 2021)
An image carries within it a series of meanings that can be explored for the creation of a company's visual communication and thus transmit to its audience through the media a visual message capable of informing about the identity, values, positioning and even about the products and services provided by the company. This work aims to analyze the visual communication of advertising pieces posted on Facebook and Instagram of companies that are linked to sustainable production and conscious consumption, aiming to identify visual elements that characterize their relationship with sustainability, using visual syntax. With the selection of five companies that present themselves in their social network as sustainable, we carried out a documental survey of their visual communication and later the categorization of the material obtained and its analysis to identify these elements with the theoretical support of authors in the area of visual syntax, photography, sustainability, conscious consumption and slow fashion. We verified the presence of a characteristic visual style in common among some companies due to the use of visual elements that carry meanings related to sustainability. Some companies have a very similar visual style in their communication, but the visual elements present in this style have no connection with sustainability. To resolve this issue, we identified which elements of visual communication are related to sustainability and which elements are directed to a specific market niche through the analysis of visual elements present in these companies' communication.
Keywords: Comunicação visual; Sustentabilidade; Consumo (Economia); Mídia social; Moda; Visual communication; Sustainability; CNPQ::CIENCIAS SOCIAIS APLICADAS